Development of an Extracurricular E-Module on Early Literacy and Numeracy to Enhance Student Engagement - Mardiana Ria; Solfema Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
This study addresses the low level of student participation in Calistung extracurricular activities at the junior high school level, which is associated with the absence of well-structured learning materials. The study aims to produce an e-module that meets validity and practicality criteria and to evaluate its effectiveness in enhancing student activeness. A Research and Development (R&D) approach was employed using the 4-D model, limited to the define, design, and develop stages. The participants were students involved in Calistung extracurricular activities at SMPN 1 VII Koto Sungai Sariak. Data were gathered through validation sheets, questionnaires, and pretest–posttest instruments. The findings indicate that the developed e-module is considered appropriate by experts, easy to use by users, and effective in increasing student activeness, as reflected in the improvement of N-Gain scores. Therefore, the e-module can serve as an alternative instructional medium to promote active student participation in extracurricular learning activities.